2014
DOI: 10.1002/ams2.71
|View full text |Cite
|
Sign up to set email alerts
|

Portable system for monitoring of regional cerebral oxygen saturation during prehospital cardiopulmonary resuscitation: a pilot study

Abstract: Aim:We aimed to create a system for monitoring of regional cerebral oxygen saturation (rSO2) in patients with prehospital cardiopulmonary arrest and clarify the changes in rSO2 during cardiopulmonary resuscitation. Methods:We measured rSO2 in cardiopulmonary arrest patients who were transferred by the emergency response vehicle of Nagasaki University Hospital. We developed a portable rSO2 monitor (HAND ai TOS), which is small enough to carry during prehospital treatment. The sensor is attached to the forehead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Both Ito et al [ 5 ] and Storm et al [ 11 ] revealed significantly higher cerebral rSO 2 values on hospital arrival in patients with a good neurological outcome, but the cerebral rSO 2 values of the good and poor outcome groups varied widely and there was a large amount of overlap. We hypothesised that a single measurement of cerebral value might not be important because the rSO 2 values always change depending on the patient’s situation at the time of the rSO 2 measurement [ 4 , 8 ]. Therefore, we think that the value of NIRS should be assessed by trend value, not by absolute value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both Ito et al [ 5 ] and Storm et al [ 11 ] revealed significantly higher cerebral rSO 2 values on hospital arrival in patients with a good neurological outcome, but the cerebral rSO 2 values of the good and poor outcome groups varied widely and there was a large amount of overlap. We hypothesised that a single measurement of cerebral value might not be important because the rSO 2 values always change depending on the patient’s situation at the time of the rSO 2 measurement [ 4 , 8 ]. Therefore, we think that the value of NIRS should be assessed by trend value, not by absolute value.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we developed a portable rSO 2 monitor (HAND ai TOS®; TOSTEC Co.), which is 170 × 100 × 50 mm in size and 600 g in weight and which is small enough to carry in the pre-hospital settings. Thus, we can now measure the pre-hospital rSO 2 values [ 8 ]. There is a need for a prospective multi-centre study that includes measurements from the pre-hospital setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We think that LDB-CPR may offer a significant beneficial effect on the maintenance of cerebral oxygenation during resuscitation. Moreover, we have developed a portable NIRS system and conducted a pilot study of the device [ 16 ]. This will allow us to evaluate changes in rSO 2 resulting from prehospital mechanical chest compression.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Our group has reported the effect of cerebral rSO 2 monitoring in patients with out-of-hospital cardiac arrest (OHCA) in resuscitation situations for several years. [6][7][8][9][10] In addition to cerebral rSO 2 , we have also recorded the hemoglobin index (HbI). The HbI is the amount of hemoglobin measured by near-infrared radiation and is determined by the measurement of light intensity received at 805 nm.…”
Section: Introductionmentioning
confidence: 99%